ASSESSMENT OF THE ROLE OF MELATONIN IN THE PATHOGENESIS OF HORMONAL INFERTILITY AND DEVELOPMENT OF A COMBINATION THERAPY SCHEME WITH ITS APPLICATION - Ikramova Kholidzhon Sakhibovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The study of melatonin levels in women of reproductive age with PCOS is a promising direction, which makes it possible to more accurately determine treatment tactics for women with PCOS with different phenotypes. The results obtained demonstrate the need to include the determination of melatonin in women of reproductive age with PCOS as an additional diagnostic criterion for making a diagnosis and determining further management tactics.